Karakteristik amplitudo akomodasi mata pada anak sekolah dasar dengan kelainan refraksi di Kabupaten Badung, Bali, Indonesia - Luh Gede Anggasari Dewi; Ariesanti Tri Handayani; Ida Bagus Putra Manuaba; Anak Agung Mas Putrawati Triningrat (Intisari Sains Medis, 2020)
Background: Amplitude of Accommodation (AA) is the maximum amount of accommodation of a person's response when looking closely. Decreased accommodation capability indicates functional abnormalities, including refractive disorders. This study aims to determine the characteristics of accommodative amplitude in elementary school children with refractive abnormalities in Badung Regency, Bali.Methods: This study was an analytic cross-sectional observational research. Data were collected prospectively based on the results of examinations and observational records of students in four elementary schools. Data were presented in frequency, percentage, and bivariate tests. Data were analyzed by SPSS version 20 for Windows.Results: Most of the study respondents were 7 years old (25.7%), female (52.7%), not wearing glasses (91.2%), bilateral myopia correction (43.2%), and having sharp vision before correction of 0.3 (0.2-0.5) diopters. There was a significant difference in binocular eye accommodation based on the comparison of Subject AA with the Expected Value (p = 0.001). However, there was no significant difference in the comparison of students' refractive errors with the amplitude of monocular accommodation (p> 0.05).Conclusion: The measurement of monocular AA decreased with age and in this study, there was no AA result that was lower than the expected value or the minimum value according to the Hofstetteer formula. AA measurement results are not affected by refractive errors. It is necessary to screen for refractive errors early in children to reduce the number of amblyopia.  Latar Belakang: Amplitudo akomodasi (AA) adalah jumlah maksimum akomodasi dari respon seseorang saat melihat dekat. Penurunan kemampuan akomodasi menunjukkan adanya kelainan fungsional antara lain  berupa kelainan refraksi. Tujuan penelitian ini untuk mengetahui karakteristik amplitudo akomodatif pada anak sekolah dasar dengan kelainan refraksi di Kabupaten Badung, Bali.Metode: Penelitian ini merupakan observasional dengan pendekatan studi potong lintang analitik. Data dikumpulkan secara prospektif berdasarkan hasil pemeriksaan dan pencatatan hasil observasi pada anak-anak di empat sekolah dasar. Data ditampilkan dalam bentuk frekuensi, persentase, dan analisis bivariat. Data dianalisis dengan SPSS versi 20 untuk Windows.Hasil: Sebagian besar responden penelitian berusia 7 tahun (25,7%), berjenis kelamin perempuan (52,7%), tidak menggunakan kacamata (91,2%), koreksi kacamata myopia bilateral (43,2%), dan memiliki tajam pengelihatan sebelum koreksi sebesar 0,3 (0,2-0,5) dioptri. Terdapat perbedaan yang bermakna akomodasi mata binokular berdasarkan perbandingan AA Subjek dengan Expected Value (p=0,001). Akan tetapi tidak terdapat perbedaan bermakna pada perbandingan kelainan refraksi siswa dengan amplitudo akomodasi monokular (p>0,05).Kesimpulan: Pengukuran AA monokular menurun sesuai usia dan pada penelitian ini, tidak terdapat hasil AA yang lebih rendah dibandingkan dengan expected value maupun nilai minimal menurut formula Hofstetteer. Hasil pengukuran AA tidak dipengaruhi oleh kelainan refraksi. Perlu dilakukan skrining kelainan refraksi lebih awal pada anak-anak untuk mengurangi jumlah ambliopia.